E-commerce contribution to customer loyalty in the textile sector, Lima, 2025 - Espinoza Quispe, Karina Yobana (2025)
Objective: This research is part of Sustainable Development Goal No. 12, which promotes responsible production and consumption. Its objective was to identify the relationship between e-commerce and customer loyalty in a Peruvian textile company located in Lima city by 2025. Materials and methods: This is an applied study with a quantitative approach, a non-experimental correlational design, and a cross-sectional. It is work a representative sample of 132 clients, who responded to a structured questionnaire with a Likert-scale questionnaire. Results: The results show a very strong, positive, and statistically significant relationship between e-commerce and customer loyalty (rho = 0.841; p = 0.000). Likewise, strong and significant positive correlations were found in the dimensions of interaction in platform, digital commercialization, and electronic transactions with the loyalty of clients. Conclusions: It is concluded that an optimized digital ecosystem contributes positively to client loyalty, so it is recommended to strengthen the digital experience, optimize logistics processes, and guarantee security in the transaction such as strategies are key for building user loyalty.